AutKom: a musical-bodily-based group training supporting adults with autism and intellectual disability. Issue 1 (1st June 2016) - Bergmann, Thomas; Herberger, Katrin; Birkner, Joana; Sappok, Tanja
Abstract : Background : Music plays an important role in education and therapy for children with autism spectrum disorder (ASD). Although ASD is a lifelong condition, music therapy is rarely reported in adults on the spectrum. There is a lack of structured concepts for supporting adults with ASD and intellectual disability (ID). Objective : We therefore developed a structured, mixed-gender group training combining an educational approach with musical-bodily interventions. Methods : A questionnaire with 57 items was developed to assess clients' needs in the field of social, emotional, and practical skills. AutKom was conducted by a pedagogue and a music therapist. Setting and flow were structured with consideration of ASD-typical features. The feasibility of the program was measured by participation rate. Results : The assessment of needs resulted in a focus on social and practical skills. During two runs, emotion and stress regulation came to the fore. Music and movement-based interventions emerged as more appropriate and effective compared to learning-theoretical principles alone. The participation rate was 84% with no dropouts. Conclusions : Musical-bodily interventions are significant in an educational group training fostering social and emotional skills in adults with ID and ASD.